Effects and interactive effects of high-altitude environment on metabolism in normal and diabetic populations: a comparative metabolomics study - Shi, Jing; Meng, Jinli; Zhang, Chenghui; Feng, Li; Wang, Suyuan; Li, Hengyan; Guo, Yongyue; Hu, Xin; Li, Xiaomei; He, Wanlin; Cheng, Jian; Wu, Yunhong (Frontiers in Endocrinology, 2026)
IntroductionHigh-altitude environments impose unique physiological stresses that may alter metabolic dysregulation in individuals with type 2 diabetes mellitus (T2DM). However, the key determinants driving altitude-specific metabolic differences in diabetic patients remain insufficiently characterized. This study aimed to identify critical metabolic biomarkers and pathways distinguishing T2DM patients residing at high versus low altitudes.MethodsSerum samples were collected from 100 participants stratified into four matched groups: high-altitude T2DM (H_T2DM), high-altitude healthy controls (H_HC), low-altitude T2DM (L_T2DM), and low-altitude healthy controls (L_HC). Metabolomic profiling was performed using ultra-performance liquid chromatography‒quadrupole time-of-flight mass spectrometry (UPLC‒Q‒TOF‒MS) to compare endogenous metabolite abundance across groups. Pathway topology analysis was conducted to annotate functional metabolic pathways, and multicenter validation was implemented to verify the robustness of candidate biomarkers.ResultsA total of 26 differentially abundant endogenous metabolites were identified in H_T2DM patients relative to the other three groups, with 18 metabolites significantly upregulated and 8 downregulated. Pipecolic acid, lauric acid, guanosine, and kaempferol were identified as potential early biomarkers for high-altitude diabetes, collectively achieving a prediction accuracy of 92%. These biomarkers were linked to core metabolic pathways including lysine degradation, fatty acid biosynthesis, and purine metabolism. Multicenter validation further confirmed guanosine as the most robust and altitude-specific biomarker for T2DM.DiscussionOur comprehensive metabolomic analysis reveals distinct metabolic perturbations in T2DM patients under high-altitude conditions, highlighting guanosine as a unique biomarker for identifying altitude-related diabetic metabolic dysregulation. These findings advance our understanding of the pathophysiological mechanisms underlying T2DM in high-altitude environments and provide a potential diagnostic target for clinical management of diabetic populations in such regions.